Expert F# 2.0 - Syme, Don (Apress, 2012)
F# is a typed functional programming language for the .NET Framework which allows you to write simple code to solve complex problems. It combines the succinctness, expressivity, and compositionality of typed functional programming with the runtime support, libraries, interoperability, tools, and object model of .NET. The aim of this book is to help you become an expert in using F# and the .NET Framework. Functional programming has long inspired researchers, students, and programmers alike with its simplicity and expressive power. Applied functional programming is booming: a new generation of typed functional languages is reaching maturity; some functional language constructs have been integrated into languages such as C#, Python, and Visual Basic; and there is now a substantial pool of expertise in the pragmatic application of functional programming techniques. There is also strong evidence that functional programming offers significant productivity gains in important application areas such as data access, financial modeling, statistical analysis, machine learning, software verification, and bio-informatics. More recently, functional programming is part of the rise of declarative programming models, especially in the data query, concurrent, reactive, and parallel programming domains. i